2019
DOI: 10.3906/sag-1803-177
|View full text |Cite
|
Sign up to set email alerts
|

Which nostril should be used for nasotracheal intubation with Airtraq NT?: the right or left? A randomized clinical trial

Abstract: Background and aim: Nasotracheal Airtraq, is specifically designed to improve the glottis view and ease the nasotracheal intubation process in normal and difficult cases. Materials and methods: After Ethics committee approval, we decided to enroll 40 patients with an ASA physical status of I or II, between 18-70 years of age undergoing elective maxillofascial, oral and double chin surgery to determine which nostril is more suitable for nasotracheal intubation with nasotracheal Airtraq. Patients were randomise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…In the discussion section, the statement that studies and case reports are available that had successfully performed all nasal intubations through the right nostril with Airtraq NT totally mismatches with regard to one of the three references cited for it. The study by Xue FS et al (cited as Ref # 7 in the current study [1]) was an observational study that had only analyzed the feasibility of Airtraq NT for orotracheal intubations (not for nasal intubations as mentioned in the article) and found that it was successful in all the 42 patients [4]. Another statement that the Airtraq NT would be produced with a left channel in the coming days to make it easier for nasal intubations through the left nostril also does not match with the three references cited for it.…”
mentioning
confidence: 74%
“…In the discussion section, the statement that studies and case reports are available that had successfully performed all nasal intubations through the right nostril with Airtraq NT totally mismatches with regard to one of the three references cited for it. The study by Xue FS et al (cited as Ref # 7 in the current study [1]) was an observational study that had only analyzed the feasibility of Airtraq NT for orotracheal intubations (not for nasal intubations as mentioned in the article) and found that it was successful in all the 42 patients [4]. Another statement that the Airtraq NT would be produced with a left channel in the coming days to make it easier for nasal intubations through the left nostril also does not match with the three references cited for it.…”
mentioning
confidence: 74%
“…1. The search of the databases yielded 113 citations, 7 RCTs 3,5,6,8,9,18,19 were included after 106 citations were excluded based on their title or abstract, improper intervention/control, duplicate studies and nonrelevant topic. Three additional RCTs 7,20,21 were identified from references within manuscripts, thus 10 RCTs met the inclusion criteria and were included in the present meta-analysis 3,5–9,18–21 …”
Section: Resultsmentioning
confidence: 99%
“…All 10 studies reported the incidence of epistaxis, 3,5–9,18–21 and five studies reported the severity of epistaxis 3,6,19–21 . Two studies reported the time to pass the tube through the nasal passage, 6,9 and three studies reported the total intubation time 5,6,9 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent article by Arslan and Türkyılmaz [1], comparing the performance of nasotracheal intubation (NTI) with the nasotracheal Airtraq® (Airtraq NT) between the right and left nostrils, they showed that NTI could be completed in a shorter time through the right nostril than through the left. Furthermore, both external laryngeal pressure and head flexion eased the NTI from the left nostril.…”
Section: To the Editormentioning
confidence: 99%